Proteomic identification and histopathological validation of candidate biomarkers CA1, HBB, Torsin A, and α-Tubulin in gingivo-buccal oral squamous cell carcinoma - Vidyarani Shyamsundar; Soundarya Ravindran; Arvind Krishnamurthy; Divyambika Catakapatri Venugopal; Yasasve Madhavan; Ananthi Sivagnanam; Anju Mayadevi Nair; Sanjana Vimal; Pallavi Kesavan; N. Senthil Subramaniyan; N. Aravindha Babu; Vijayalakshmi Ramshankar (Frontiers in Medicine, 2026)
Background Gingivo-buccal oral squamous cell carcinoma (GB-OSCC) represents one of the most prevalent tobacco-associated malignancies in India and is frequently diagnosed at advanced stages with poor clinical outcomes. Despite the high disease burden, validated specific biomarkers for gingivo-buccal cancers remain limited. The current study aimed to identify and validate protein biomarkers associated with disease progression and aggressive pathological features in GB-OSCC using an integrated proteomic and immunohistochemical (IHC) approach. Methods Proteomic discovery analysis was performed on pooled fresh-frozen tumor tissues obtained from 40 histologically confirmed GB-OSCC patients categorized into four groups based on clinical stage and treatment outcome: early-stage no evidence of disease (NED), early-stage failure, advanced-stage NED, and advanced-stage failure ( n = 10/group). Differential protein expression profiling was carried out using two-dimensional gel electrophoresis (2DE) followed by matrix-assisted laser desorption/ionization-time of flight mass spectrometry. Functional enrichment and protein interaction analyses were performed using PANTHER and STRING databases. Four candidate proteins—Carbonic Anhydrase 1 (CA1), Hemoglobin subunit beta (HBB), Torsin A, and α -Tubulin—were selected for validation by immunohistochemistry in retrospective formalin-fixed paraffin-embedded tissues comprising healthy controls, oral epithelial dysplasia, and GB-OSCC cases ( n = 125). Results Proteomic analysis identified 37 differentially upregulated proteins associated with tumor progression, cytoskeletal remodeling, metabolic regulation, and angiogenesis. STRING network analysis demonstrated enrichment of proteins involved in glycolysis, apoptosis signaling, keratinization, and cellular regulatory pathways. IHC validation revealed progressive overexpression of CA1, HBB, Torsin A, and α -Tubulin across the spectrum from healthy mucosa to dysplasia and invasive carcinoma. Increased expression of CA1 and HBB showed significant associations with tumor size, degree of differentiation, muscle invasion, lymphovascular invasion, depth of invasion, invasive tumor front characteristics, and tumor budding. Torsin A and α -Tubulin expression correlated significantly with advanced histopathological grade, invasive behavior, and aggressive tumor phenotypes. Receiver operating characteristic (ROC) curve analysis showed that HBB and CA1 have significant area under the curve (AUC) indicating good discriminatory ability for SCC detection. Conclusion This study identifies and validates a subsite-specific protein biomarker panel for gingivo-buccal OSCC in an Indian cohort. The combined overexpression of CA1, HBB, Torsin A, and α -Tubulin demonstrates potential utility in identifying aggressive disease biology and may contribute toward improved prognostic stratification and translational biomarker development in tobacco-associated oral cancers. Larger multicentric studies are warranted to establish their clinical applicability.